Peningkatan Motivasi Belajar Siswa Melalui Aplikasi Game Quizizz Mode Paper Pada Pembelajaran Tematik Tema 8 Di Kelas V SDN 08 Mataram Tahun Ajaran 2022/2023 - Fitriana, Indah Nur; Fatmawati, Elisa; Darmiany, Darmiany (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research aims to increase students' learning motivation using the quizizz paper mode game application in thematic learning theme 8 in class V at SDN 08 Mataram in the 2022/2023 academic year. This type of research is classroom action research. Data collection methods use questionnaires, documentation and tests. The types of data used are qualitative data and quantitative data. The research subjects were class V students at SDN 08 Mataram with a total of 27 students. The general research results show an increase in the percentage of students' learning motivation, namely in the pre-cycle the percentage was 60% with the sufficient category (C), then in the first cycle it increased to 76% with the good category (B) and increased to 84% in the second cycle with the good category. (B) which means that the Quizizz paper mode game application is very effective for increasing learning motivation for class V students at SDN 08 Mataram for the 2022/2023 academic year.